CXCL16 associates with adverse outcome and cardiac involvement in hospitalized patients with Covid-19. Issue 6 (December 2022) - Gregersen, Ida; Ueland, Thor; Holter, Jan Cato; Olsen, Maria Belland; Michelsen, Annika E; Murphy, Sarah L; Tveita, Anders Aune; Henriksen, Katerina Nezvalova; Hoel, Hedda; Nordberg, Lena Bugge; Holten, Aleksander Rygh; Edvardsen, Thor; et al.
Highlights: CXCL16 correlates to severity of Covid-19. CXCL16 associates with cardiac risk markers. CXCL16 predicts risk of 60 days mortality.